Respon Guru Dan Siswa Terhadap E-Modul Gelombang Bunyi Berbantuan Aplikasi Phyphox Untuk Meningkatkan Kemandirian Dan Hasil Belajar Siswa Kelas XI IPA MAN 2 Lubuklinggau - Wahyu Arini; Ramadhan Fitriyani (Science and Physics Education Journal (SPEJ, 2023)
Abstract: The research of this study was to see the response of teachers and students after participating in learning using the sound wave e-module assisted by the Phyphox application. The research method used is descriptive research type. The subjects of this study were physics teachers and students of class XI IPA MAN 2 Lubuklinggau. The data collection technique was carried out in the form of a response questionnaire. The results of the physics teacher's response analysis obtained 74% with the "Positive" criterion. The results of the analysis of student responses in small groups of 9 students were obtained with a percentage of 71%, included in the "Positive" criteria and the results of student response analysis in large group trials with a total of 23 students, so that a percentage of 71% was obtained, this percentage was included in the criteria of "Positive" . Based on the research data obtained, it can be concluded that the sound wave e-module assisted by the Phyphox application gets a good response in learning activities. Keywords: Phyphox, E-module,Sound Wave, Response